Development of E-Comic Teaching Materials for Social Studies Learning in Elementary Schools - Hana Dinah Fadilah (Profesi Pendidikan Dasar, 2021)
The purpose of this research is to develop mobile learning-based e-comic social studies teaching materials to pique the interest of fifth-graders in elementary school. The students in this study are from the fifth grade at Riyadh El Jannah Islamic School. The ADDIE model is used to conduct research development or research and development in this study. However, it only reaches the development stage due to circumstances that prevent it from completing all of the stages. This research used a questionnaire for expert evaluation as well as interviews with teachers and students. This study employed descriptive quantitative and descriptive qualitative data analysis techniques. The quantitative descriptive method is used to process expert data and student response questionnaires, while the qualitative descriptive method is used to describe corrective comments and validators' inputs. The feasibility test for mobile learning-based e-comic teaching materials received an average percentage of 93.78 percent, making it a worthy category. The final scores for product trials on teacher and student responses were 92 percent and 94.57 percent, respectively. Based on the findings of the data analysis, it can be concluded that the developed mobile learning-based e-comic teaching materials are suitable for classroom use